2019
DOI: 10.1097/cm9.0000000000000247
|View full text |Cite
|
Sign up to set email alerts
|

Impact of obstructive sleep apnea on pulmonary hypertension in patients with chronic obstructive pulmonary disease

Abstract: Background: Chronic obstructive pulmonary disease (COPD) and obstructive sleep apnea (OSA) syndrome are highly prevalent respiratory conditions. Their coexistence is referred to as the overlap syndrome. They are both related to pulmonary hypertension (PH) development. This study investigated the effects of OSA on PH in patients with COPD and the associated factors. Methods: Consecutive patients with stable COPD were recruited for an observational cross-sectional study f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 49 publications
2
24
0
Order By: Relevance
“…In a recent study, authors from China examined 106 patients with COPD and found that pulmonary artery pressure (PAP) was increased by 5 mmHg in the group of patients with the OS (52.8%) compared with COPD only patients. The increase in PAP positively correlated with reduced mean SpO 2 levels during the night [21].…”
Section: Clinical and Cardiovascular Consequencesmentioning
confidence: 85%
See 1 more Smart Citation
“…In a recent study, authors from China examined 106 patients with COPD and found that pulmonary artery pressure (PAP) was increased by 5 mmHg in the group of patients with the OS (52.8%) compared with COPD only patients. The increase in PAP positively correlated with reduced mean SpO 2 levels during the night [21].…”
Section: Clinical and Cardiovascular Consequencesmentioning
confidence: 85%
“…In contrast, other studies investigated the prevalence of the OS in OSA and COPD respectively with highly variable prevalence figures reported depending on the diagnostic techniques employed but with more than half of patients with COPD were found to have associated OSA [21,22]. In a cross-sectional study on a large number of patients, the OS was the final diagnosis in 12% of patients diagnosed with OSA [23].…”
Section: Epidemiologymentioning
confidence: 93%
“…A major study examining the prevalence of OSA was the 1993 Wisconsin Sleep Cohort Study, which found that OSA is prevalent in approximately 4% of men and 2% of women among the middle-aged population and increases with age [ 1 ]. The prevalence is thought to range from 28% to 72% in elderly men and 20% to54% in elderly women [ 7 ]. These numbers are rough estimates and thought to be falsely low given how often OSA is undiagnosed [ 2 ].…”
Section: Reviewmentioning
confidence: 99%
“…There are several factors that increase the risk of both PH and OSA, such as older age, obesity, left-sided heart disease, parenchymal lung disease, and nocturnal desaturation. The level of the pulmonary artery pressure correlates with the severity of OSA [5,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral edema and emphysema have been reported to predict OSA, 13,14 but the predictive values of age, sex, body mass index (BMI), neck circumference, and smoking status remain controversial. 15,16 Further investigations are therefore needed to clarify the roles of these factors in predicting OSA. Furthermore, a better understanding of the important risk factors and clinical outcomes of patients with overlap syndrome in different geographical areas would help the relevant health authorities to implement targeted intervention strategies.…”
mentioning
confidence: 99%